A abordagem de temas polêmicos no currículo da EJA: o caso do “florestamento" no RS - Forgiarini, Marcia Soares (2007)
The present research was carried through in the line of Curriculum, Education and Practical pertaining to school of the Program of Pos-graduation in Education of the Universidade Federal de Santa Maria/RS. Initially, I argue that, amongst the many existing problems, in the Education, which need to be faced, one of the most accentuated, particularly in the EJA, is the disentail between the "world of the school" and the "world of the life". Being this problem unleash of others, such as: mere preliminary education, discouragement, the absence of meaning attributed to that if it makes in the school, the low level of knowledge and the reinforcement at culture of the silence . Its comprehended that its possible overcome this release by means of curricular configurations marked out with themes. Thus, it was assumed as theoretician s referenciais: presuppositions of the Brazilian educator Paulo Freire, the movement of Society-Technological-Science, as well as of the Portuguese educator Pedro Reis, which work with the category controversial themes. This work deals with a research of qualitative matrix, more specifically, a study of case in relation to the repercussion of the theme "forestation" in the RS, in the curriculum of the EJA. In this, the inquiry problem was defined by the questioning: which has been the repercussion of the theme "forestation" in the RS, in the curriculum of the EJA? The objective consisted of investigating and identifying possibilities and challenges to be faced in relation to the implementation of this theme in the curriculum of four schools, situated in cities with intense plantations of monocultures to this big project, in phase of implantation in the State. The questions of the research had been: 1) Why the forestation in RS did not re-echo in the EJA s curriculum? and 2) Which the challenges and possibilities of studying this theme, called controversial, in EJA s curriculum? The used instruments, for attainment of the "data", had been: registers written under the form of Diary; questionary and interviews. Of the analysis of the results, it had the identification of five categories that constitute challenges to be faced, which are: 1) Formation excessively broken up, disentailed of the context, 2) Absence of convictions, of accurate answers in relation the controversial aspects of the theme, 3) "Something more", 4) Neutrality of the Teacher and, 5) Professor of Formation or Professor of Information. In terms of signalling of the research, it is distinguished that, for the overcoming of the separation it enters the "world of the school" and the "world of the life", has the overcoming necessity, in the curriculums of majors courses, of the broken up formation, to discipline solely, disentailed of the problems of every day life, considering that the complexity of the contemporaries problems is not attained for such formation